Optimizing Tourism Potential and Superior Products of Sanjai Tourism Village Through Website Design and Implementation - Rifki Suwandi; Arrya Anandika; Rian Ferdian; Tati Erlina; Ratna Aisuwarya; Budi Rahmadya; Dodon Yendri; Werman Kasoep; Rahmi Eka Putri; Nefy Puteri Novani; Desta Yolanda; Rizka Hadelina (Warta Pengabdian Andalas, 2025)
The use of technology is fundamental in the digital era. Adjustment and transformation are essential activities to keep up with technological developments. One of the uses of technology is product marketing and promotion. Sanjai Tourism Village, located in Bukittinggi City, is one of the villages where marketing and promotion of tourism products are still carried out using conventional promotional methods such as through newspapers, radio advertisements, posters, and distribution of brochures. This method is still limited and cannot reach a broader scope. Therefore, to compete in the digital era, there needs to be a transformation of promotion and marketing of tourism products through the internet media using a website. Information about promoting and marketing tourism products can be done digitally and online using a website. The results of advertising and marketing tourism village products by utilizing the website can be spread and known to the public with a broader reach. Therefore, in the community service activities of the Unand Computer Engineering Department, the Sanjai Tourism Village website was built with a method consisting of several stages, such as coordination, surveys, design, website implementation, improvement, and submission of the website to Sanjai Tourism Village. Each stage has been carried out, and a website has been produced with features such as a homepage, profile, tourism products of various fields, news and activities, and contacts.